1997
DOI: 10.1111/j.1440-1746.1997.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in Helicobacter pylori seroprevalence in Singapore: Correlation with differences in peptic ulcer frequency

Abstract: The aim of this study was to determine, first, whether racial differences exist in the seroprevalence of Helicobacter pylori infection in Singapore, and second, whether these differences correlate with racial differences in peptic ulcer frequency. A commercial serological test for immunoglobulin (Ig)G antibody to H. pylori which was 90% sensitive and 83% specific in our population was used to screen 403 adult blood donors of Chinese, Malay and Indian origin, aged between 15-60 years. Serum specimens from 84 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
1
21
1
Order By: Relevance
“…This is in agreement with the findings of Boey et al (3) for asymptomatic Malaysian children: the rate of seropositivity increased with age, and seropositivity was most common among the Indian children. A study by Kang et al (15) demonstrated that racial differences in the seroprevalence of H. pylori were more pronounced in the adult population. The study also showed that Indians had the highest prevalence of infection, followed by Chinese and Malay, but the Indian subjects had a lower frequency of peptic ulcer disease than the Chinese subjects (15).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the findings of Boey et al (3) for asymptomatic Malaysian children: the rate of seropositivity increased with age, and seropositivity was most common among the Indian children. A study by Kang et al (15) demonstrated that racial differences in the seroprevalence of H. pylori were more pronounced in the adult population. The study also showed that Indians had the highest prevalence of infection, followed by Chinese and Malay, but the Indian subjects had a lower frequency of peptic ulcer disease than the Chinese subjects (15).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of H. pylori infection in the Singapore adult population shows a distinct ethnic pattern. It is present in 70% of Indians, 43% of Chinese, and 36% of Malays [2]. The ethnic differences in gastric cancer frequency, therefore, cannot be explained by H. pylori infection alone, and may possibly be caused by host-bacterial interaction factors [3].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The HEL-pII Test kit utilizes the enzyme-linked immunosorbent assay (ELISA) technique for the detection of antibodies to H. pylori. This ELISA kit has been evaluated in our laboratory on a series of local patients with known H. pylori histological status, with a demonstrated sensitivity of 90.2% and specificity of 83.3% [13]. Serum gastrin level was measured by radioimmunoassay, using the Gamma Dab [ 125 I] Gastrin Radioimmunoassay Kit (DiaSorin, Stillwater, MN, USA).…”
Section: Introductionmentioning
confidence: 99%